Islam, Feminisme, dan Gender: Pesrpektif Tafsir Maudhu’i - Fathurrohman, Aceng; Al Rifai, Agna Fikri; Darma, Astri Aisyah (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2024)
The feminism movement has become one of the most important debates in Muslim conversations. In fact, the Qur'an, as a guide for Muslims, has already discussed this issue. This article explores the interpretation of Qur'anic verses related to feminism issues. By analyzing Qur'anic verses related to gender and the role of women in society, this article tries to explain how Islamic understanding of the concept of gender equality can contribute to the issue of feminism. Through a review of various Qur'anic interpretations, this article attempts to understand the theological frameworks used by scholars to address the challenges and perspectives of feminism. This research provides an in-depth insight into the complex dynamics between Islamic teachings and feminist struggles. By considering the views of various scholars and diverse Qur'anic interpretations, this article seeks to provide a foundation for Islam and feminism in achieving gender equality.